Prevalence Of Early Childhood Caries, Malocclusion And Ameloblastoma In Children And Radiographic Findings Of Ameloblastoma In A Known Population - Lamba, Gagandeep; Thota, Lavanya; Thota, Gunaranjan; Bajpai, Ranjan; Malde, Nidhi; Jain, Archana (Journal of Neonatal Surgery, 2025)
Background: This study was conducted to assess the Prevalence of Early Childhood Caries and Malocclusion in Children and, Radiographic Findings of Ameloblastoma in a known population. Material and methods: This study comprised of 100 participants aged from 2 years to 15 years. The parents of the children were informed about the study procedure. All the parents agreed to give consent and hence, all the participants were included in the study. The children underwent oral clinical examination. The prevalence of early childhood caries and malocclusion were noted and the findings were tabulated. The children suspected for ameloblastoma underwent radiographic examination. All the radiographic findings observed had been noted down. Statistical analysis was conducted using SPSS software. Results: In this study, there were total 100 children of which 49 belonged to the age group of 2-5 years, 26 belonged to the age group of 6-10 years and 25 belonged to the age group of 11-15 years. Early childhood caries was seen in 33 children. Malocclusion was seen in 47 children and ameloblastoma was seen in 20 children. Out of 47 children, type I, type II and type III malocclusion were seen in 16,23 and 8 children, respectively. The chief radiographic findings seen in children with ameloblastoma were multilocular radiolucency, cortical expansion towards both cheek and tongue, root resorption and ill-defined margins. Conclusion: Based on the findings of this study, it can be concluded that the prevalence of early childhood caries, malocclusion and ameloblastoma in children was 33%, 47% and 20%, respectfully. The chief radiographic findings seen in children with ameloblastoma were multilocular radiolucency, cortical expansion towards both cheek and tongue, root resorption and ill-defined margins.